Processing, Characteristics, and Potential Application of Red Palm Oil - A review - Kartika Okta Purnama; Dwi Setyaningsih; Erliza Hambali; Darmono Taniwiryono (International Journal of Oil Palm, 2020)
Crude palm oil (CPO) is produced from the extraction process of palm fruit pulp. Palm oil contains essential components in the form of triglycerides, mostly as fatty acids, namely palmitic acid, oleic, and linoleic. However, palm oil also contains minor phytonutrients, such as carotene, tocopherol, and tocotrienol. Palm oil has been widely used in the food and non-food industries. As a raw material in various products, palm oil undergoes a refinery process to remove unlike free fatty acids (FFA), odors, and colors (reddish to bright yellow). In this process, phytonutrients are degraded and damaged so that the content becomes very low. Phytonutrients in the CPO has not been fully utilized their benefits for human health. One of the palm oil products that contain high phytonutrient compounds is red palm oil. There are two types of red palm oil, namely virgin red palm oil (VRPO) and red palm oil derived from CPO (RPO). VRPO is produced from direct extraction of oil palm fruit, while RPO is produced from the neutralization of CPO and deodorization at low temperatures to reduce FFA levels. Both of these products contain high phytonutrients, such as carotene, tocopherol, and tocotrienol. This paper reviews several studies on the processing, characteristics, and potential use of red palm oil in food and non-food products. The application of red palm oil in margarine as a specific food product has the potential to be further studied.